MWCNTs/PEDOT: PSS Composite as Guiding Layer on Screen-Printed Carbon Electrode for Linear Range Lactate Detection. Issue 3 (10th March 2021) - Ali, Muhsin; Khalid, Muhammad Asad Ullah; Kim, Young Su; Soomro, Afaque Manzoor; Hussain, Saddam; Doh, Yang Hoi; Choi, Kyung Hyung
Abstract : The emerging field of nanomaterials could be utilized in biosensors for addressing challenging applications due to its abundant strategic properties. Herein, a composite of multi-walled carbon nanotubes (MWCNTs) and poly (3, 4-ethylene dioxythiophene)-poly(styrene sulfonate) (PEDOT: PSS) was synthesized, and used as guiding layer on screen printed carbon electrode (SPCE) for lactate detection. Lactate plays a substantial role in health care applications. Fundamental characteristics of the composite modified SPCE were studied using FE-SEM, EDS, and Raman spectroscopy and sensor performance was analyzed by electrochemical methods. AFM was used to thoroughly study the screen-printed carbon electrode and as-deposited MWCNT/PEDOT:PSS composite film topography. Various parameters were optimized to achieve the best performance of lactate sensor. The developed sensor provided a wide linear range response (R 2 = 0.97) from 1 mM to 10 mM for buffer samples with 35.224 μ A mM −1 sensitivity. The proposed sensor was applied for to detect lactate in cancer (MCF-7) cells media. A calculated LOD 4.0 ± 5 μ M (S/N) was achieved and the results showed a linear response up to 7 mM. As a result, the advanced approach could be applied for the detection of a range of metabolites using respective enzymes. This approach could open on-line lactate detection in organ-on-a-chip applications.